"Fibroblast" pharmacotherapy — Advancing the next generation of therapeutics for clinical cardiology. (May 2016) - Eadie, Ashley L.; Simpson, Jeremy A.; Brunt, Keith R.
Highlights: All three compartments of RAS (circulating, tissue and intracellular) are critical in the pathogenesis of heart failure. Fibroblasts are active, not passive, endocrine regulators of ECM remodeling that are regulated by RAS. Fibroblasts synthesize chymase, an essential modulator of RAS activity, which affects modulating cardiac ECM. Only 2 of 8 drug classes are widely used to manage RAS; future therapeutics are targeting chymase as a key regulator of RAS.